Ketamine disrupts locomotion and electrolocation in a novel model of schizophrenia, Gnathonemus petersii fish - Langova, Veronika; Horka, Petra; Hubeny, Jan; Novak, Tomas; Vales, Karel; Adamek, Petr; Holubova, Katerina; Horacek, Jiri (Journal of neuroscience research, 2023)
The present study aimed to examine a weakly electric fish Gnathonemus petersii (G. petersii) as a candidate model organism of glutamatergic theory of schizophrenia. The idea of G. petersii elevating the modeling of schizophrenia symptoms is based on the fish's electrolocation and electrocommunication abilities. Fish were exposed to the NMDA antagonist ketamine in two distinct series differing in the dose of ketamine. The main finding revealed ketamine-induced disruption of the relationship between electric signaling and behavior indicating impairment of fish navigation. Moreover, lower doses of ketamine significantly increased locomotion and erratic movement and higher doses of ketamine reduced the number of electric organ discharges indicating successful induction of positive schizophrenia-like symptoms and disruption of fish navigation. Additionally, a low dose of haloperidol was used to test the normalization of the positive symptoms to suggest a predictive validity of the model. However, although successfully induced, positive symptoms were not normalized using the low dose of haloperidol; hence, more doses of the typical antipsychotic haloperidol and probably also of a representative of atypical antipsychotic drugs need to be examined to confirm the predictive validity of the model.
Keywords: schizofrenie; Haloperidol; ketamin; haloperidol; Locomotion; zvířata; Ketamine; elektrické ryby; Schizophrenia; Electric Fish; lokomoce; Animals